Strategi Pembinaan Karakter Mandiri dan Disiplin Santri di Pondok Pesantren - Tri Rahayu; Husnul Bahri (Indonesian Journal of Character Education Studies, 2025)
Background: Islamic boarding schools play a vital role in providing religious education and fostering character development among students. One of the main aspects of character building is discipline and independence. The Darussalam Islamic Boarding School in Bengkulu City, Bengkulu, implements a development strategy that aims to shape students who are independent and disciplined, despite facing challenges from environmental factors surrounding the boarding school. Objective: This study aims to analyze the strategies for developing discipline and independence implemented at the Darussalam Islamic Boarding School, and to evaluate the effectiveness of these strategies in shaping the character of students. Method: This study employs a qualitative approach, utilizing a case study method. Data was collected through in-depth interviews, participatory observation, and documentation. Data analysis was conducted thematically. Results: Discipline and independence are fostered through educational sanctions, such as cleaning the environment and participating in physical activities. This guidance is practical in fostering student awareness, although it is influenced by internal and external factors, such as family background and the environment surrounding the boarding school. Conclusion: Guidance at Darussalam Islamic Boarding School is practical; however, challenges from the external environment require attention. Contribution: This study contributes to the development of a more modern and relevant character-building model in Islamic boarding schools.